Multislice helical computed tomography imaging diagnosis and surgical treatment of primary tracheal tumor in cardiothoracic surgery - Rui, Jun; Lian, Yu (Frontiers in Oncology, 2024)
Objective: it aimed to explore the value of multislice helical computed tomography (MSCT) in the diagnosis and surgical treatment of primary tracheal tumors. Methods: 64 patients with the primary tracheal tumor who were diagnosed in Wuxi Second People's Hospital from March 2020 to March 2021 were selected as the research objects. MSCT imaging was performed on all patients, and suitable surgical methods. The pathological results were compared with original CT, CT virtual endoscopy (CTVE), and Comparisons were made using CT three-dimensional reconstruction images to evaluate the accuracy of MSCT diagnosis. Parameters such as postoperative complications and survival rates were observed to assess surgical effectiveness and safety. Results: Compared with original CT images (70%, 72%, 70%), the diagnostic accuracy of VR images (80%, 80%, 80%), MPVR images (85%, 90%, 92%), and CTVE images (100%, 100%, 100%) was remarkably improved (P<0.05). The three-year survival rate of patients with smooth muscle tumors, malignant tumors, salivary gland adenoma, papillary tumors, and inflammatory polyp was markedly lower than that of the one-year survival rate, with a significant difference (P<0.05). The incidence of postoperative complications was 14.1%, with three cases resulting in complication-related deaths. Conclusion: the diagnostic accuracy of MSCT imaging of primary tracheal tumor was high. The diagnostic accuracy of CTVE was higher than that of VR and MPVR. Besides, surgical treatment of primary tracheal tumor had a substantial effect, with no serious postoperative complications.